Maintaining social well-being and meaningful work in a highly automated job market - Hai-Jew, Shalin (IGI Global, 2020)
""This book explores cutting -edge thinking about how the world will re-shape as one with less demand for human labor and how to potentially balance how people engage the world as part-workers and as consumers' of others' creations"--Provided by publisher"--